Research progress of PYK2 in digestive system diseases - Duan, Yiyao; Xie, Mingzhu; Wang, Hui; Chen, Sijing; Hu, Jun; Chen, Xujia; Ping Jia, Hong; Zhang, Ningyan; Peng, Ling; Li, Xiang; Khan, Hameed Ullah; Hu, Die; et al. (Frontiers in Immunology, 2025)
Belonging to the focal adhesion kinase (FAK) family, proline-rich tyrosine kinase 2 (PYK2) is a non-receptor tyrosine kinase, has become a focal point in cancer research owing to its essential participation in the formation and dissemination of tumors. Studies have shown that this kinase controls various cellular activities, including: tumor cell adhesion, growth, multiplication, specialization, and detachment, making it a promising target for developing anticancer drugs. The goal of this review is to analyze the multifaceted role of PYK2 in gastrointestinal disease, focusing on its contribution to tumor progression, associated signaling pathways, and the therapeutic potential of PYK2 inhibitors in improving disease management and prognosis.